Profitability and Multi-functionality of Integrated Enterprise Model Cattle Farming in Coastal Region of Bangladesh: A Socio-Economic Analysis - Ahmed, Salim; Alam, Mohammad Fakhrul; Huda, Fakir Azmal (Research in Agriculture Livestock and Fisheries, 2025)
This study aimed to assess the profitability of cattle farming with non-conventional by-product utilization, understand the economic benefits of livestock multi-functionality, and identify challenges in livestock farming in coastal Bangladesh. A quantitative, cross-sectional, survey-based research design was employed. The study was conducted in the Khulna, Satkhira, and Bagerhat districts of coastal Bangladesh between November 2024 and January 2025. Data were collected from 120 randomly selected cattle farmers across 12 villages through face-to-face interviews using a pre-tested schedule. Data analysis involved descriptive statistics, farm budgeting techniques (Net Farm Income, Management Income), and a Problem Facing Index (PFI) to evaluate constraints. The integration of non-conventional by-products (cow dung stick, vermicompost, biogas) significantly enhanced profitability. Biogas integration yielded the highest Net Farm Income (BDT 316,632.10) and Management Income (BDT 124,132), representing a 47.51% and 76% higher income, respectively, compared to business-as-usual practices (NFI BDT 166,200.85; MI BDT 30,431.75). Farmers strongly perceived livestock's contribution to soil fertility (85% agreement) and food & nutrition (80% agreement). The primary challenges identified were disease occurrence (PFI: 310/360) and high feed prices (PFI: 285/360) in traditional systems, while bad odor (PFI: 260/360) and labor availability (PFI: 250/360) were key issues in integrated models. Multi-functional livestock farming, especially with biogas integration, is a highly profitable enterprise that substantially boosts household income, food security, and environmental sustainability in coastal Bangladesh. It offers a viable pathway for climate change mitigation through the valorization of manure. Policy interventions focused on increasing awareness, providing soft loans for technology adoption, and improving veterinary services are crucial for scaling these benefits. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 161-173